Aflasafe MWMZ01 and Aflasafe MW02 for Malawi - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
In December 2018 Malawi’s Agricultural Technical Clearing Committee approved Aflasafe MWMZ01 and Aflasafe MW02 for release and use by farmers. In 2020, the two products were officially registered with the Pesticides Control Board of Malawi.